2021
DOI: 10.1098/rsta.2020.0330
|View full text |Cite
|
Sign up to set email alerts
|

How latex film formation and adhesion at the nanoscale correlate to performance of pressure sensitive adhesives with cellulose nanocrystals

Abstract: Emulsion polymerized latex-based pressure-sensitive adhesives (PSAs) are more environmentally benign because they are synthesized in water but often underperform compared to their solution polymerized counterparts. Studies have shown a simultaneous improvement in the tack, and peel and shear strength of various acrylic PSAs upon the addition of cellulose nanocrystals (CNCs). This work uses atomic force microscopy (AFM) to examine the role of CNCs in (i) the coalescence of hydrophobic 2-ethyl hexyl acrylate/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 78 publications
3
26
0
Order By: Relevance
“…There are reports that sulfated CNCs lower the solids content threshold for latex particle coalescence, thereby promoting film formation. [ 24 ] The same phenomenon was observed in this work as can be seen from the larger polymer islands on AFM images of samples with increasing cCNC loadings (Figure 2B,C) versus those without (Figure 2A). Processing these AFM images through a computer vision approach [ 19 ] revealed that the films produced from 0.35 wt.% latex samples containing 0.5 phm cCNCs (regardless of cCNC type or dispersion method) displayed between 10.8 and 14.6% surface coverage, whereas the film without cCNCs only had a surface coverage of 6.1% ( Table 2 ).…”
Section: Resultssupporting
confidence: 86%
“…There are reports that sulfated CNCs lower the solids content threshold for latex particle coalescence, thereby promoting film formation. [ 24 ] The same phenomenon was observed in this work as can be seen from the larger polymer islands on AFM images of samples with increasing cCNC loadings (Figure 2B,C) versus those without (Figure 2A). Processing these AFM images through a computer vision approach [ 19 ] revealed that the films produced from 0.35 wt.% latex samples containing 0.5 phm cCNCs (regardless of cCNC type or dispersion method) displayed between 10.8 and 14.6% surface coverage, whereas the film without cCNCs only had a surface coverage of 6.1% ( Table 2 ).…”
Section: Resultssupporting
confidence: 86%
“…A significant reduction in tack was observed for PSAs prepared with CNC–M at both loadings, consistent with the poor initial dispersion of CNC–M in the monomer phase that results in the presence of large CNC aggregates in the film (Figure C) . The addition of CNC–W improved the tack of PSAs when introduced at 1 phm loading, but no significant increase in the tack was observed at a lower loading of 0.5 phm at which the improvement in the contact angle due to CNC–W addition was only minimal (Figure A and Table ).…”
Section: Results and Discussionsupporting
confidence: 56%
“…For example, when CNC–monomer compatibility is suboptimal, such as with 2-ethylhexyl acrylate (EHA) (a monomer that has a low water solubility of <0.001 g L –1 ), CNC aggregation during film formation results in poor PSA properties compared to formulations with less-hydrophobic monomers. , On the other hand, Yu et al incorporated CNCs modified with 3-methacryloxypropyltrimethoxysilane (fCNCs) in situ into EHA-containing latexes and observed significantly improved adhesive properties relative to unmodified CNCs, which was attributed to the ability of fCNCs to copolymerize with the bulk polymer due to the presence of reactive vinyl groups on the silane that effectively compatibilize the CNC–PSA interface . Similarly, Pakdel et al reported that “less hydrophilic” CNCs (produced by CelluForce Inc., product grade: CNC-103) with lower surface charge density, and higher surface activity resulted in CNCs that were better dispersed in the latex and facilitated uniform PSA film formation, leading to improved tack and peel strength compared to unmodified CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…To study film formation, stepwise temperature control was applied because the film formation of latex coatings is typically more complex than that of solvent-based polymer coatings. In general, film formation involves (1) the evaporation of water, followed by (2) the closed packing and deformation of latex particles, and (3) the formation of a transparent film by interdiffusion of polymer chains, as illustrated in Scheme . The evaporation of water leads to the close packing of the particles, followed by the deformation of the particles owing to a combination of capillary, osmotic, and surface forces. This typically occurs above the minimum film formation temperature (MFFT) .…”
Section: Methodsmentioning
confidence: 99%